2019
DOI: 10.1039/c9an00112c
|View full text |Cite
|
Sign up to set email alerts
|

Insulin: a review of analytical methods

Abstract: Insulin is an important polypeptide hormone that regulates carbohydrate metabolism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
69
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(73 citation statements)
references
References 68 publications
0
69
0
4
Order By: Relevance
“…Calcium–phosphate product concentration was calculated as calcium concentration × phosphate concentration. Serum insulin levels were measured by using a chemiluminescence immunoassay [ 23 ], with intra-assay coefficients of variation of 2.5% at 43.1 pM and 1.2% at 423 pM. We computed HOMA-IR and HOMA-β scores, using the following formulas: HOMA-IR = (fasting insulin (μU/mL) × fasting glucose (mg/dL))/405 [ 24 ] and HOMA-β = 360 × (fasting insulin/(fasting glucose − 63)) [ 24 ].…”
Section: Methodsmentioning
confidence: 99%
“…Calcium–phosphate product concentration was calculated as calcium concentration × phosphate concentration. Serum insulin levels were measured by using a chemiluminescence immunoassay [ 23 ], with intra-assay coefficients of variation of 2.5% at 43.1 pM and 1.2% at 423 pM. We computed HOMA-IR and HOMA-β scores, using the following formulas: HOMA-IR = (fasting insulin (μU/mL) × fasting glucose (mg/dL))/405 [ 24 ] and HOMA-β = 360 × (fasting insulin/(fasting glucose − 63)) [ 24 ].…”
Section: Methodsmentioning
confidence: 99%
“…Insulin, which has an N -terminal Phe residue on its B-chain, is a peptide hormone integral in glucose regulation and metabolism with important implications in the diagnosis and treatment of diabetes. Various analytical methods for insulin detection have been studied including immunoassays 6 and MS; 7 however, these techniques require expensive and bulky on-site instrumentation. Recent studies in optical detection methods have been based on surface plasmon resonance 8 and fluorescence resonance energy transfer, 9 but these methods rely on broad spectral signatures not specific to the molecular fingerprint of the analyte.…”
Section: Introductionmentioning
confidence: 99%
“…Considering the mentioned limitations, a comparison of this method with earlier published assays showed that the present method is to some extent less sensitive, but by using high resolution mass spectrometry the qualitative (and quantitative) result interpretation is very strong. 5,11,12,21,22 Additionally, the simultaneous determination of C-peptide in the same assay enables a more comprehensive result.…”
Section: Proof Of Conceptmentioning
confidence: 99%